Validation and Experimental Evaluation of Magnetorheological Brake-by-Wire System - Abdullah, M. A.; Zainordin, A. Z.; Hudha, K. (Journal of Engineering and Technology (JET), 2013)
Magnetorheological brake is one of x-by-wire system which is performing better than conventional brake system. MR brake consists of a rotating disc that is immersed with magnetorheological fluid in an enclosure of an electromagnetic coil. The applied magnetic field will increase the yield strength of the MR fluid where this fluid was used to decrease the speed of the rotating shaft. The purpose of this paper is to develop a mathematical model to represent MR brake with a test rig. The MR brake model is developed based on actual torque characteristic which is coupled with motion of a test rig. Next, the experimental are performed using MR brake test rig and obtained three output responses known as angular velocity response,torque and load displacement. Furthermore, the MR brake was subjected to various loads and current. Finally, the simulation results of MR brake model are verified with experimental results.